2012
DOI: 10.2190/om.65.3.c
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining Relational Continuity with the Deceased on Facebook

Abstract: Scholars have noted that communication helps maintain relational continuity despite physical absence; yet, the specific role of communication in continuing a relationship with the deceased has not been analyzed. In this study, messages directed to the deceased on Facebook memorial group walls were examined to explore how grieving individuals utilize Facebook memorial groups in order to make sense of the death of a loved one and reconnect with the deceased. Using a grounded theory approach, message topics and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(87 citation statements)
references
References 26 publications
4
81
0
2
Order By: Relevance
“…As previously discussed, because SNSs offer a place to rapidly connect with other mourners, create and share tributes, give or receive social support, or simply observe others' griefwork, they have become popular locations to memorialize deceased celebrities (e.g., Radford & Bloch, 2013;Sanderson & Cheong, 2010) as well as personal friends and family members (Carroll & Landry, 2010;DeGroot, 2012;Frost, 2014;Kern et al, 2013). In the same vein, SNSs also provide a convenient and relatively public platform for individuals to channel their grief into proactive efforts to advance social causes endorsed by the celebrity or in honor of the celebrity, such as donating to charities (e.g., Brown, 2010), or in the case of the current study, educating others with health-related information or directives such as suicide prevention advice (e.g., Krysinska & Andriessen, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously discussed, because SNSs offer a place to rapidly connect with other mourners, create and share tributes, give or receive social support, or simply observe others' griefwork, they have become popular locations to memorialize deceased celebrities (e.g., Radford & Bloch, 2013;Sanderson & Cheong, 2010) as well as personal friends and family members (Carroll & Landry, 2010;DeGroot, 2012;Frost, 2014;Kern et al, 2013). In the same vein, SNSs also provide a convenient and relatively public platform for individuals to channel their grief into proactive efforts to advance social causes endorsed by the celebrity or in honor of the celebrity, such as donating to charities (e.g., Brown, 2010), or in the case of the current study, educating others with health-related information or directives such as suicide prevention advice (e.g., Krysinska & Andriessen, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…SNSs such as Twitter and Facebook have made a variety of mourning rituals more accessible to people grieving personal friends and loved ones as well as those grieving public figures. These platforms give users the opportunity to pay respects and express their grief, to give and provide social support by interacting with others who are bereaved, or to simply reduce loneliness by observing others' grief and feeling a part of a larger community of mourners (Carroll & Landry, 2010;DeGroot, 2012;Frost, 2014;Kern, Forman, & Gil-Egui, 2013). Studies have found that following Michael Jackson's death, grieving fans used Twitter to memorialize the late pop star, and to share information and emotional support with others (Lee & Goh, 2013;Sanderson & Cheong, 2010).…”
Section: Rituals Of Mourning For Celebritiesmentioning
confidence: 99%
“…However, this can provide an important stimulus to counselling sessions or interview processes, and this type of follow-up could provide more details about why particular comments were posted and how this affected their grief (DeGroot, 2012).…”
Section: Challenges For Schools -Policies For Social Networkingmentioning
confidence: 99%
“…Whilst there are growing bodies of research examining death and commemorative practices online (see Brubaker & Haynes, 2011) and social networking sites (see DeGroot, 2012;Rossetto, Lannutti, & Strauman, 2014), there is a paucity of research focusing specifi cally on Aboriginal people's use of social media for death and funeral practices. In this article, we draw from extensive interview data to explore some of the emerging practices associated with death and mourning made possible by social media.…”
Section: Introductionmentioning
confidence: 99%